Downhole geophysical data acquisition during reverse circulation drilling for mining. Issue 1 (1st December 2019) - Hopper, Timothy; Schubert, Matthew; Joldes, Grand; Moran, Brendan; Kalisch, Paul; Crumby, Mark; Buters, Nick; Ott, Kai-Uwe; Rogozinski, Kamil; Morgan, Quentin; Neville, Tom; Shanmugam, Harish; et al.
Summary: Measurement While Drilling (MWD) and Logging While Drilling (LWD) tools acquire geophysical and operational data from directly behind the bit during drilling operations. Traditionally, such tools have only been integrated into mud rotary drilling systems used in the oil and gas industry and are not available to the mining industry, where reverse circulation (RC) is the prevalent drilling method. A joint venture between Wallis Drilling and Qteq was formed to develop tools that acquire geophysical data while using RC drilling systems. In this paper, we present drillMAX, the world's first MWD tool for use in RC drilling.